PENGARUH SUPPORT BASED RELATIONSHIPS TERHADAP KEPUASAN KERJA DAN PEMBERDAYAAN KARYAWAN SEBAGAI PEMEDIASI (Studi Kasus PT.Bank SUMUT di Kota Medan) - Winda Ardiani; Rizky Putra (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2017)
This study aimed to analyze the influence of internal organizational relations and employee-customer relationship to job satisfaction through empowerment of employees. The method used in this study is a survey approach, this type of research is quantitative descriptive analytical method used is the analysis of the path, with 3 (three) the hypothesis being tested. The results of the study on the first hypothesis, it is known that simultaneously internal organizational relations and employee-customer relationships significantly influence employee empowerment. But partially employee-customer relationship and no significant effect on the empowerment of employees. For the second hypothesis, based on the partial test known that employee empowerment significant effect on job satisfaction. For the third hypothesis, based on the partial test in the know that the connection relationship of internal organization and employee empowerment, variables significantly influence job satisfaction, employee empowerment variables are variables that most influence on job satisfaction compared with a variable internal organizational relationships.Keywords: Support Based Relationships, Job Satisfaction, Employee Empowerment